Upregulated Lipid Biosynthesis at the Expense of Starch Production in Potato (Solanum tuberosum) Vegetative Tissues via Simultaneous Downregulation of ADP-Glucose Pyrophosphorylase and Sugar Dependent1 Expressions - Xu, Xiaoyu; Vanhercke, Thomas; Shrestha, Pushkar; Luo, Jixun; Akbar, Sehrish; Konik-Rose, Christine; Venugoban, Lauren; Hussain, Dawar; Tian, Lijun; Singh, Surinder; Li, Zhongyi; Sharp, Peter J.; et al. (Frontiers in Plant Science, 2019)
Triacylglycerol is a major component of vegetable oil in seeds and fruits of many plants, but its production in vegetative tissues is rather limited. It would be intriguing and important to explore any possibility to expand current oil production platforms, for example from the plant vegetative tissues. By expressing a suite of transgenes involved in the triacylglycerol biosynthesis, we have previously observed substantial accumulation of triacylglycerol in tobacco (Nicotiana tabacum) leaf and potato (Solanum tuberosum) tuber. In this study, simultaneous RNAi downregulation of ADP-glucose pyrophosphorylase and Sugar-dependent 1, was able to increase the accumulation of triacylglycerol and other lipids in both wild type potato and the previously generated high oil potato line 69. Particularly, a 16-fold enhancement of triacylglycerol production was observed in the mature transgenic tubers derived from the wild type potato, and a two-fold increase in triacylglycerol was observed in the high oil potato line 69, accounting for about 7 % of tuber dry weight, which is the highest triacylglycerol accumulation ever reported in potato. In addition to the alterations of lipid content and fatty acid composition, sugar accumulation, starch content of the RNAi potato lines in both tuber and leaf tissues were also substantially changed, as well as the tuber starch properties. Microscopic analysis further revealed variation of lipid droplet distribution and starch granule morphology in the mature transgenic tubers compared to their parent lines. This study reflects that the carbon partitioning between lipid and starch in both leaves and non-photosynthetic tuber tissues, respectively , are highly orchestrated in potato, and it is promising to convert low-energy starch to storage lipids via genetic manipulation of the carbon metabolism pathways.